A Generalized Two–Scale Approximation for Ocean Wave Models - Perrie, William; Toulany, Bechara; Casey, Michael (Frontiers in Marine Science, 2022)
The two-scale approximation (hereafter, TSA) was previously presented as a new method to approximate and estimate transfer rates in wind – wave spectra. It was shown to perform well for a variety of idealized and observed sea state conditions and to compare well with respect to the total Boltzmann integral for nonlinear quadruplet wave-wave interactions. Here, we present a generalized formulation of TSA, allowing for multiple peaked spectra, sheared spectra, sea – swell combinations, etc. This formulation is implemented in a modern operational wave model, WAVEWATCHIII™, and shown to provide a significant improvement over the standard approximation used in wave models, the discrete interaction approximation (DIA). Additional tests involve the simulation of waves generated in Hurricane Teddy (2020).